Relationship between primary health care quality and dental caries in preschoolers - Beatriz Díaz Fabregat; Eliane Cristina Gava Pizi; Juliane Avansini Marsicano; Rosana Leal do Prado (Editorial Ciencias Médicas, 2021)
Introduction: Primary health care solves most of the health problems of the population, provides primary access to the service, ensures the continuity and comprehensiveness of health care, and coordinates its different forms. Objective: Evaluate the relationship between primary health care quality and dental caries in preschoolers. Methods: A cross-sectional descriptive study was conducted of a sample of 515 preschoolers. Participant schools were selected by stratified random sampling, followed by simple random sampling for the selection of participant children. Oral examination was performed to evaluate dental caries, and parents / guardians were given a questionnaire about the quality of the primary services attended by their children. Data were estimated with the chi-squared test, the Wilcoxon test and Spearman's coefficient (95% confidence). Results: A relationship was found between primary health care quality and the ceod index of preschoolers (ρ = -0.19; p < 0.05). Significant differences were observed in the prevalence of dental caries when quality services (ceod = 0.50) were compared with the low quality group (ceod = 1.13). Quality was also associated to the service mode (p < 0.001). Private services and the family health strategy obtained higher quality scores (55.31% and 69.48%, respectively). Conclusions: Primary health care quality is closely related to oral health, in such a way that when the quality of primary health care services is not good, a higher dental caries rate is observed among preschoolers.